Comportamiento a flexión pura de muros de mampostería en arcilla, reforzados con barras de FRP (2017)
Due to the interest in the Colombian environment to be at the vanguard with the latest available technologies and materials, a research project was proposed in order to evaluate the flexion capacity of clay masonry, reinforced with FRP bars at perpendicu-lar loads to plane, and take the first step to generate a preliminary design protocol for the future based on the ACI 440 and TMS402 / ACI 530, Being that there is no design guide yet to contemplate the behavior of masonry under this approach. The experimental program included the construction and test of 16 masonry walls in clay, seven walls were reinforced with Glass fiber Reinforced Polymer (GFRP) bars, and the other seven were reinforced with CFRP Carbon fiber Reinforced polymer, and the remaining two were reinforced with conventional steel rods. The variables that were taken into account in the investigation were the dimensions of the wall in plan and the rebar. The walls were tested in a test frame which had a length between supports of 2030 mm and loaded the walls with two concentrade loads in the thirds along the wall, looking for a pure bending behavior in the central third. A very similar behavior of the analytical model was observed, compared to the experimental results for service loads. As for the ultimate loads, differences were found between theory and tests.